Formula Romansa dalam novel Remember When karya Judith McNaught - Lanipi, Novelista; Wantasen, Isnawati L.; Sebayang, F. Ari A. (Kajian Linguistik, 2026)
This research aims to analyze the romance formula in Judith McNaught’s Remember When by applying Cawelti’s (1976) theory of plot structure and Radway’s (1984) theory of ideal romance. The objectives are to identify the romance formula presented in the novel and to examine how the plot constructs this formula. A descriptive qualitative method is employed, with data collected through intensive reading and note-taking and analyzed by categorizing story elements according to Radway’s thirteen stages of the ideal romance narrative and Cawelti’s four structural elements of plot, followed by an interpretation of their contributions. The results reveal that the romance formula in Remember When consistently aligns with Radway’s thirteen ideal stages, with the most dominant stage being element twelve, in which the female character responds both sexually and emotionally. The plot structure effectively develops and reinforces this formula through sequential conflicts and resolutions. This research contributes to literary studies, particularly in the analysis of popular romance narratives, and serves as a reference for future narrative research. Keywords: romance formula; plot structure; popular romance; Remember When